Risk management in radiation therapy with SEVRRA - Geórgia Santos Joana; Marcello Gomes Gonçalves; Camila Salata; Flávia Cristina Teixeira; Emmilly Sandrini; Guilherme Bittencourt; Helio Salmon; Leandro Fairbanks; Saulo Santos Fortes; Maria do Socorro Nogueira (Brazilian Journal of Radiation Sciences, 2018)
ABSTRACT